Increased Fecal Lactobacillus Is Associated With a Positive Glucose Hydrogen Breath Test in Bangladeshi Children - Donowitz, Jeffrey R (Open Forum Infect Dis, 2019)
BACKGROUND: Glucose hydrogen breath testing is a noninvasive test for small intestine bacterial overgrowth (SIBO). A positive glucose hydrogen breath test is common in children from low-income countries and has been found to be associated with malnutrition as measured by stunted growth. The microbiome associated with positive breath testing is relatively unstudied. METHODS: We performed 16 S V4 rDNA microbiome analysis on the stool of 90 Bangladeshi children aged 2 years from an impoverished neighborhood who were tested at the same time for SIBO by glucose hydrogen breath testing. Data were analyzed by linear discriminant analysis effect size with SIBO as the outcome. Any selected genera were tested individually by Wilcoxon’s rank-sum test to ensure that linear discriminant analysis effect size results were not outlier-skewed. RESULTS: Linear discriminant analysis effect size analysis identified Lactobacillus (linear discriminate analysis score, 4.59; P = .03) as over-represented in 15 out of the 90 children who were SIBO positive. CONCLUSIONS: These results suggest that glucose hydrogen breath test positivity in children from low-income settings may be due to an upper intestinal Lactobacillus bloom, potentially explaining the association of SIBO with the gut damage and inflammation that leads to malnutrition.